50 Jahre / Years documenta 1955-2005 : diskrete Energien = discreet energies - Museum Fridericianum, Kassel (Kassel : Documenta Archiv Kassel Museum Fridericianum Kassel, 2005)
Ahtila, Eija-Liisa ; Anselmo, Giovanni ; Applebroog, Ida ; Art & Language ; Baer, Jo ; Bayrle, Thomas ; Beckett, Samuel ; Beuys, Joseph ; Bhimji, Zarina ; Bijl, Guillaume ; Bissier, Julius ; Blume, Bernhard Johannes ; Boltanski, Christian ; Cage, John ; Camnitzer, Luis ; Capa, Robert ; Carroll, Lawrence ; Christo ; Clark, Lygia ; Copley, William ; Duchamp, Marcel ; van der Elsken, Ed ; Emshwiller, Ed ; Evans, Walker ; Fautrier, Jean ; Filliou, Robert ; Fischli & Weiss ; Fontana, Lucio ; Fox, Terry ; Goldstein, Malcolm ; Graham, Rodney ; Grimonprez, Johan ; Grossarth, Ulrike ; Haacke, Hans ; Hamilton, Richard ; Handke, Peter ; Hartung, Karl ; Heldt, Werner ; Henry, Pierre ; Hermanns, Ernst ; Hockney, David ; Kagel, Mauricio ; Kitaj, R.B. ; Klossowski, Pierre ; Knowles, Alison ; Kriwet, Ferdinand ; Lehmbruck, Wilhelm ; Maciunas, George ; Manzoni, Piero ; Martin, Agnes ; Matta-Clark, Gordon ; Michaux, Henri ; Modersohn-Becker, Paula ; Morley, Malcolm ; Nauman, Bruce ; Oldenburg, Claes ; Paik, Nam June ; Pasolini, Pier Paolo ; Raetz, Markus ; Richter, Gerhard ; Roth, Dieter ; Ruscha, Edward ; Ruthenbeck, Reiner ; Scholte, Rob ; Schoonhoven, Jan ; Siegelaub, Seth ; Smithson, Robert ; Spero, Nancy ; Tansey, Mark ; Thek, Paul ; Thomkins, André ; Tobey, Mark ; Trökes, Heinz ; Uhlmann, Hans ; Vieira da Silva, Maria Elena ; Weegee ; Wegman, William ; Winter, Fritz ; Wodiczko, Krzysztof ; Wölfli, Adolf ; Wols
bibliog. p. 223-226
biog. p. 210-222
Duits, Engels
Exhibition. 50 Jahre / Years documenta 1955-2005. Museum Fridericianum Kassel. 2005-09-01. 2005-11-20
boek